2014
DOI: 10.1186/1471-2180-14-153
|View full text |Cite
|
Sign up to set email alerts
|

The oxygen sensor MgFnr controls magnetite biomineralization by regulation of denitrification in Magnetospirillum gryphiswaldense

Abstract: BackgroundMagnetotactic bacteria are capable of synthesizing magnetosomes only under oxygen-limited conditions. However, the mechanism of the aerobic repression on magnetite biomineralization has remained unknown. In Escherichia coli and other bacteria, Fnr (fumarate and nitrate reduction regulator) proteins are known to be involved in controlling the switch between microaerobic and aerobic metabolism. Here, we report on an Fnr-like protein (MgFnr) and its role in growth metabolism and magnetite biomineralizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…This suggests that the expression of MgFnr was neither affected by iron addition nor by different DO levels studied, indicating that the magnetite biomineralization may also be regulated by other unknown oxygen sensors. Our finding is in agreement with Li et al 2014, where MgFnr was only involved in the expression of denitrification genes but not genes encoding oxygen respiration enzyme. The authors therefore concluded that MgFnr plays an indirect role in maintaining proper redox conditions required for magnetite biomineralization.…”
Section: Genes Associated With Oxygen Metabolismsupporting
confidence: 92%
See 3 more Smart Citations
“…This suggests that the expression of MgFnr was neither affected by iron addition nor by different DO levels studied, indicating that the magnetite biomineralization may also be regulated by other unknown oxygen sensors. Our finding is in agreement with Li et al 2014, where MgFnr was only involved in the expression of denitrification genes but not genes encoding oxygen respiration enzyme. The authors therefore concluded that MgFnr plays an indirect role in maintaining proper redox conditions required for magnetite biomineralization.…”
Section: Genes Associated With Oxygen Metabolismsupporting
confidence: 92%
“…MgFnr was reported as an oxygen sensor with the role of controlling magnetite biomineralization by regulation of denitrification in MSR-1 cells (Li et al 2014). In the current study, however, there is no significant (p < 0.05) difference in expression level of MgFnr between the three oxygen conditions throughout fermentations.…”
Section: Genes Associated With Oxygen Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…[28,37,38] We demonstrate that arrays genetically stitched together of up to five GusA monomers plus an additional mEGFP can be fused as a large hybrid protein to a single MamC anchor protein. Purified magnetosome particles exhibited mEGFP fluorescence and a stable, up to 2.8-fold increased specific activity compared to monomeric GusA protein expressed as single-copy magnetosome fusions.…”
Section: Introductionmentioning
confidence: 90%